Multiple sclerosis and depression - Feinstein, Anthony (Multiple sclerosis, 2011)
Clinically significant depression can affect up to 50% of patients with multiple sclerosis over the course of their lifetime. It is associated with an increased morbidity and mortality and is regarded by patients as one of the main determinants of their quality of life. This review summarizes current perspectives relating to diagnosis, the utility of self report screening questionnaires, warning signs of suicidal intent and the biological and psychosocial variables implicated in mood change. In particular, the association between depression and structural brain abnormalities, including those derived from diffusion tensor imaging, is highlighted. Depression is treatable, as the results from randomized controlled trials of antidepressant medication, cognitive behavior therapy and mindfulness therapy, reveal. These positive findings are offset by data showing that depression in a neurological setting is often overlooked and under treated.